Supply chain resilience for global operations (1) : a rethink for a new paradigm (part II : transportation sector) - Koh, Choon Chin (Nanyang Technological University, 2021)
The Covid-19 crisis has placed tremendous amount of stress on the supply chain management within the transportation sector. Faced with unprecedented lockdowns and simultaneous shocks from both the demand and supply side, transportation providers must swiftly adapt to both environments as they struggle to keep up with surge in consumer online shopping and home deliveries whilst ensuring the reliability of their services as these new bottlenecks emerge.This research paper discusses the paradigm shift in global agri-food companies’ supply chain management and how they evolved due to the Coronavirus.In the past, supply chain optimization strategies have been the focus of many companies seeking to reduce costs along the supply chain. Such strategies help to reduce inventory and maximize asset utilization. But this strategy also concurrently deteriorated buffers within the value chain and companies’ resilience to react against unprecedented supply chain disruptions. The worldwide impacts of the COVID-19 pandemic created stresses and bottlenecks in the supply chain such as food processing, transportation,and retailers due to the implementation of policies and changes in human behaviors.This report aims to examine the various transportation sector strategies used in response to the pandemic and through an analysis of the opportunities and threats of these policies implemented, recommend strategies for transportation providers to react to new business environments and changing consumer behaviors in the future.